ACCOUNTING OF THE VARIABLE RESISTANCE OF CONCRETE AT AN EARLY AGE DURING THE MODELING OF LINING VERTICAL SHAFTS - Borshchevskyi, S. V. (Science and Transport Progress, 2008)
The combined technological chart for building of vertical shafts is analysed. The influence of strength properties of hardening concrete on interactions of the system «timber – massif» is explored by means of numerical simulation. The recommendations on perfection technology for timbering of deep shafts with a purpose of providing the durability and non-repair maintenance of shafts in the process of their exploitation are offered.